Outcome after neoadjuvant chemotherapy in young breast cancer patients: a pooled analysis of individual patient data from eight prospectively randomized controlled trials - Loibl, Sibylle; Jackisch, Christian; Lederer, Bianca (Breast cancer research and treatment, 2015)
Young women with breast cancer (BC) have a worse survival partly due to more aggressive tumor characteristics; however, their response to chemotherapy seems better. We investigated to what extent the prognostic factor pathological complete remission (pCR) after neoadjuvant chemotherapy is applicable to young women. 8949 patients with primary BC and follow-up from eight German neoadjuvant trials were included. A subgroup of 1453 patients <40 years was compared with women aged 40-49 and ≥50 years regarding pCR (ypT0 ypN0), as well as disease free survival (DFS), local recurrence free survival (LRFS), distant disease free survival (DDFS), and overall survival (OS) overall, according to pCR status and subtypes defined by hormone-receptor (HR) status and HER2. pCR was strongly associated with age without a clear age cut-off. The pCR rate was significantly higher in the young compared with other age groups (20.9 vs. 17.7 vs. 13.7 %; p < 0.001). This difference was confined to triple-negative breast cancer (TNBC) and HR +/HER2−. DFS, DDFS, LRFS, and OS were significantly worse for young women. Age was independently prognostic for survival in HR +/HER2−, with women <40 years without pCR having a worse DFS compared to their counterparts with pCR. Young women are more likely to achieve pCR after neoadjuvant chemotherapy, especially in HR +/HER2− and TNBC. Age is not an important prognostic factor in TNBC and HR−/HER2 + but is in HR +/HER2−. Young women with a luminal-like BC seem to benefit more from neoadjuvant chemotherapy than older women, which needs to be taken into account.